The moral value of time - ORTIZ, PEDRO (2004)
Persons are the only living beings who might consciously ascribe some value to the nature and those things they make, because their lives depends on it. As a consequence of its cultural development, particularly of its economic structure, our society has privileged territorial property, and people overvalued things more than their proper actions. This situation implies a lesser valuation of life as it should be appreciated thorough the measure of time. It is evident that the level of valuation of time varies from one economic structure to another. In the underdeveloped countries like ours, the minute valuation of time is clearly shown in unpunctuality and the irrational waste of time instead of studying and labor. An historical explanation of this kind of limitation in our personal development, instead of considering unpunctuality as a idiosyncratic characteristic of our people, should make us to reconsidered about the value of time, which is, actually, the valuation of our own life, and what we mean in terms of our value for everybody else.